Combining heat and altitude training to enhance temperate, sea-level performance - Girard, O.; Peeling, P.; Racinais, S.; Périard, J. D. (International Journal of Sports Physiology and Performance, 2024)
Background: Repeated exposure to heat (ie, plasma volume expansion) or altitude (ie, increase in total hemoglobin mass), in conjunction with exercise, induces hematological adaptations that enhance endurance performance in each respective environment. Recently, combining heat and altitude training has become increasingly common for athletes preparing to compete in temperate, sea-level conditions.